A debreceni Kossuth Lajos Tudományegyetem archontológiája (1950–1990) IV. rész - Mudrák, József (Gerundium, 2015)
ARCHONTOLOGY OF LAJOS KOSSUTH UNIVERSITY IV.: INSTITUTE OF HISTORY (1950–1990). he archontology of the Arts and Sciences Faculties of Lajos Kossuth University -the so-called central units of the university between Januar1, 1950–December 31, 1990 was prepared on the basis of the personal and personnel files of the Administration Department supported by the annual documentation of the Adminsitration from the fless documented 1950s. he exisiting materials are not complete, therefore the preparation of a comprehensive archontology is not possible. Part III. demonstrates the complete and detailed teacher and satf list of the Institute of History from the oice director to the administrators.